Drivers of spatial and seasonal variations of CO2 and CH4 fluxes at the sediment water interface in a shallow eutrophic lake. (15th August 2022) - Sun, Heyang; Yu, Ruihong; Liu, Xinyu; Cao, Zhengxu; Li, Xiangwei; Zhang, Zhuangzhuang; Wang, Jun; Zhuang, Shuai; Ge, Zheng; Zhang, Linxiang; Sun, Liangqi; Lorke, Andreas; et al.
Highlights: CO2 and CH4 concentrations in sediment enhanced by nutrients and temperature. Sediment – water fluxes increased with nutrient availability from inflow to outflow. CO2 and CH4 fluxes from the sediment share similar drivers. Sediment – water fluxes were not the major pathway for atmospheric emissions. Eutrophication and warming increase greenhouse gas fluxes from the sediment. Abstract: Shallow eutrophic lakes contribute disproportional to the emissions of CO2 and CH4 from inland waters. The processes that contribute to these fluxes, their environmental controls, and anthropogenic influences, however, are poorly constrained. Here, we studied the spatial variability and seasonal dynamics of CO2 and CH4 fluxes across the sediment-water interface, and their relationships to porewater nutrient concentrations in Lake Ulansuhai, a shallow eutrophic lake located in a semi-arid region in Northern China. The mean concentrations of CO2 and CH4 in porewater were 877.8 ± 31.0 µmol L −1 and 689.2 ± 45.0 µmol L −1, which were more than 50 and 20 times higher than those in the water column, respectively. The sediment was always a source of both gases for the water column. Porewater CO2 and CH4 concentrations and diffusive fluxes across the sediment-water interface showed significant temporal and spatial variations with mean diffusive fluxes of 887.3 ±124.7 µmol m −2 d −1 and 607.1 ± 68.0 µmol m −2 d −1 for CO2 and CH4, respectively. The temporal and spatial variations of CO2 and CH4 concentrations in porewater were associated with corresponding variations in dissolved organic carbon and dissolved nitrogen species. Temperature and dissolved organic carbon in surface porewater were the most important drivers of temporal variations in diffusive fluxes, whereas dissolved organic carbon and nitrogen were the main drivers of their spatial variations. Diffusive fluxes generally increased with increasing dissolved organic carbon and nitrogen in the porewater from the inflow to the outflow region of the lake. The estimated fluxes of both gases at the sediment-water interface were one order of magnitude lower than the emissions at the water surface, which were measured in a companion study. This indicates that diffusive fluxes across the sediment-water interface were not the main pathway for CO2 and CH4 emissions to the atmosphere. To improve the mechanistic understanding and predictability of greenhouse gas emissions from shallow lakes, future studies should aim to close the apparent gap in the CO2 and CH4 budget by combining improved flux measurement techniques with process-based modeling. Graphical abstract: Image, graphical abstract